Minecraft : stories from the overworld. - Larson, Hope; Panetta, Kevin; North, Ryan, 1980-; Roberts, Rafer, 1976-; McCranie, Stephen, 1987-; Flynn, Ian, 1982- (Dark Horse Books, 2019)
"With tales of witch and pillager rivals finding common ground, a heartless griefer who bit off more than they could chew, and valiant heroes new (or not!) to the Overworld, this anthology tells tales that span the world of Minecraft. Featuring stories from star writers Hope Larson, Kevin Panetta, Rafer Roberts, and Ian Flynn and exciting artists Meredith Gran and more, this collection brings together stories from all realms, leaving no block unturned!"--